2009
DOI: 10.3201/eid1505.081186
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficilein Ready-to-Eat Salads, Scotland

Abstract: Of 40 ready-to-eat salads, 3 (7.5%) were positive for Clostridium diffi cile by PCR. Two isolates were PCR ribotype 017 (toxin A-, B+), and 1 was PCR ribotype 001. Isolates were susceptible to vancomycin and metronidazole but variably resistant to other antimicrobial drugs. Ready-to-eat salads may be potential sources for virulent C. diffi cile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 11 publications
7
78
0
1
Order By: Relevance
“…Among the behavioral factors occurring in the community that may put females at risk of CDI are higher rates of antimicrobial prescriptions (27,28), vegetable consumption (29), and contact with children (30). While there is no conclusive evidence that contaminated food leads to CDI in humans, studies have found that retail vegetables are contaminated with C. difficile strains similar to those affecting humans (31,32). Likewise, the C. difficile ribotypes frequently isolated in the current study, such as 014/020 and 056, are common ribotypes found in piglets and veal calves, respectively, in Australia (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Among the behavioral factors occurring in the community that may put females at risk of CDI are higher rates of antimicrobial prescriptions (27,28), vegetable consumption (29), and contact with children (30). While there is no conclusive evidence that contaminated food leads to CDI in humans, studies have found that retail vegetables are contaminated with C. difficile strains similar to those affecting humans (31,32). Likewise, the C. difficile ribotypes frequently isolated in the current study, such as 014/020 and 056, are common ribotypes found in piglets and veal calves, respectively, in Australia (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these strains were of ribotypes associated with C. difficile infection in humans and food animals (RODRIGUEZ-PALACIOS et al, 2007;BAKRI et al, 2009;SONGER et al, 2009). It is also important to note that the two most common toxigenic ribotypes in pigs, which account for 90% and 80% of isolates, respectively, are also recognized as causes of C. difficile disease in humans (ARROYO et al, 2007).…”
Section: ----------------Elisa (%)----------------Pigletsmentioning
confidence: 99%
“…As such, preharvest interventions to control food-borne pathogens on the farm are predicted to decrease the frequency of carcass contamination, therefore enhancing food safety (33). Clostridium difficile spores of epidemic genotypes have been isolated from retail meats (36,38,44) and vegetables (2,4,29) and from neonatal and young cattle and pigs (32,39,42). However, the patterns of fecal C. difficile shedding among cattle during the finishing period, including the prevalence at the time of harvest, and the frequency of bovine carcass contamination have not been reported.…”
Section: /Cdtbmentioning
confidence: 99%